Shots at goal in Australian Football: Historical trends, determinants of accuracy and common strategies - Dwyer, D. B.; Young, C. M. (Journal of Science and Medicine in Sport, 2024)
Objectives To understand the historical context of and relationships between, the characteristics of shots at goal and match outcome in the Australian Football League.